Pharmacoepidemiology, impacts of anxiety disorders and anxiolytic abuse before and during the COVID-19 pandemic (Research, Society and Development, 2022)
Anxiety Disorders (AD) have gained prominence in recent years due to the increasing number of patients with this diagnosis worldwide. EDs have a higher incidence in older patients, being more prevalent in women. Studies correlate this increase with exacerbated external and internal pressures, rhythm, and lifestyle. The COVID-19 pandemic has contributed significantly to this increase. In this sense, to alleviate anxious episodes, improve sleep quality, or increase productive performance, the demand for anxiolytics has increased considerably worldwide, including Brazil. Anxiolytics act on the Central Nervous System (CNS), however, the abusive use of these psychoactive substances can cause neurological damage. Knowing this, the present work aims to analyze scientific publications to identify the main impacts of anxiety and the evolution of anxiolytic abuse before and during the COVID-19 pandemic, as well as pharmacoepidemiologic aspects of medicines against ED through a review narrative, descriptive and retrospective literature. For this, a non-exhaustive bibliographic review was carried out based on the review of scientific articles and data published between the period 2011 and 2021. Statistical analyzes were carried out according to the nature of the variables, using the appropriate tests to differentiate the groups independent in studies. Our results express an increasing number of ED diagnoses during the COVID-19 pandemic, as well as the irrational and abusive use of anxiolytics in Brazil.